EXPLORING THE IMPACTS OF TECOMELLA UNDULATA MEDIATED SILVER NANOPARTICLES ON MALE RATS FERTILITY AND REPRODUCTIVE HEALTH: A PATH TO REVERSIBLE MALE CONTRACEPTION - BHARTI, NEHA; YADAV, PRITY; KANSOTIYA, ASHISH KUMAR; MALI, PRATAP CHAND (International Journal of Current Pharmaceutical Research, 2025)
Objective: The present study was designed to evaluate the antifertility effects of AgNPs synthesized using Tecomella undulata methanolic leaf extract in male albino Wistar rats. Methods: The AgNPs were synthesized and characterized by UV-visible spectrophotometry, FTIR, XRD, SEM-EDX and ZETA potential. The antifertility effects of AgNPs were evaluated, dividing 40 male rats into five treatment Groups, G-I treated with sterile distilled water and G-II, G-III and G-IV with 10, 20 and 30 mg/kg. B. wt/D of T. undulata AgNPs doses for 60 days. Followed by analysis of sperm parameters, fertility, reproductive organ and body weight, testosterone assays and other reproductive health parameters. Results: The characterization results indicated successful synthesis of AgNPs by their size, shape, crystallinity, elements and stability results. Antifertility activity of AgNPs, showed significant reductions in sperm parameters (P<0.05) and fertility, with minimal adverse effects on body weight and haematological parameters. Degenerative changes were observed in histoarchitecture of testis. Testosterone level was affected across various dose levels (P<0.01) and markedly reduction in tissue protein, cholesterol and sialic acid was observed. These parameters show a significant recovery in treatment Group-V. Conclusion: These findings suggest that AgNPs synthesized using T. undulata possess promising antifertility potential and can be used as a promising contraceptive agent.